Employee Well Being in Education: A Systematic Literature Review of Determinants, Mediating and Moderating Roles, and Measurements Instruments - Rizki Faiz Kurniawan; Abdul Mujib; Yunita Faela Nisa (Dinasti Review, 2026)
Employee well-being in the teaching profession is a critical aspect in maintaining the quality of learning, the effectiveness of educational processes, and the sustainability of education systems amid increasing job demands and the evolving dynamics of educational policies. This study aims to systematically synthesize empirical findings on the factors influencing employee well-being among educators, as well as the patterns of relationships between individual, organizational, and socio-spiritual factors in shaping workplace well-being.This study employs a Systematic Literature Review (SLR) method guided by the PRISMA framework. The literature search was conducted across Google Scholar, Web of Science, Garuda, and Semantic Scholar databases, supported by the Publish or Perish software, while the article screening process was carried out using Covidence. Of the 512 articles initially identified, 20 met the inclusion criteria and were analyzed thematically. The findings indicate that employee well-being is influenced by individual, social, and organizational factors, while spirituality and religiosity also play a role as sources of work meaning and psychological buffers. In addition to functioning as a dependent variable, employee well-being can also act as a mediator and moderator in various work-related outcomes. Measurement of well-being across the reviewed studies was conducted using various instruments, such as the Employee Well-Being Scale (EWBS), Job-Related Affective Well-Being Scale (JAWS), Ryff’s Psychological Well-Being Scale (RPWB), and the Teacher Subjective Well-Being Questionnaire (TSWQ), reflecting diverse conceptual perspectives on workplace well-being.